ANALISIS INTESITAS CAHAYA PADA AREA PRODUKSI SHORTENING TERHADAP KESELAMATAN DAN KENYAMANAN KERJA KARYAWAN DI PT. X - Anton Pirdaus Bangun; Mhd. Fiza Lubis; Muhammad Fazri (Bajang Institute, 2025)
In the industrial world, employee safety and comfort are crucial aspects that cannot be ignored. One factor that significantly affects these aspects is adequate workplace lighting. This study aims to evaluate the impact of light intensity and eye complaint factors on worker safety and comfort and provide recommendations for companies with lighting that does not meet the standards of the Indonesian Minister of Health Regulation No.70 of 2016. The research method involves regression analysis and data collection through observation in the form of questionnaires and light measurement data, processed quantitatively, conducted at PT. X. Questionnaire results analyzed with linear regression testing indicate that light intensity in the shortening packaging and control rooms at PT. X negatively impacts employee safety and comfort, with a total effect of 80.8%. Based on direct measurements using a light intensity measurement tool (lux meter), the light intensity conditions in the shortening packaging and control rooms range from 103–267 lux. This intensity level does not meet the standard of 300 lux for production rooms, as stated in the Indonesian Minister of Health Regulation No.70 of 2016. Thus, the company needs to control light intensity to prevent accidents and discomfort among employees caused by inadequate lighting conditions